Scientific dissemination during the Covid-19 pandemic: Contributions from the Academic League of Neurosciences of the Federal University of Espírito Santo - Conceição Gama, Marcus Vinicius; Oliveira Patricio da Silva, Bruna; Toledo Nogueira, Marjorie; Silva Pinheiro, Deborah; Paranha dos Santos, Larissa; Moraes de Ornelas Carletti, Isis; Willian Hollais, André; Ferreira Pereira de Araujo, Mariana (Guará Journal, 2022)
The Neuroscience Academic League of the Federal University of Espírito Santo (LANUFES) was created during the COVID-19 pandemic, amid the need to foster new scientific dissemination strategies and provide reliable information about neuroscience and, whenever possible, its interface with the current health crisis. Given the above, the objective of this paper is to describe LANUFES’s scientific dissemination efforts in neuroscience during the pandemic. Throughout its first year of operation, LANUFES focused its efforts on systematically disseminating topics related to neuroscience and COVID-19 through publications on the social network Instagram and the promotion of virtual scientific events open to the public, in addition to holding regular scientific meetings with members. By the end of its first year, LANUFES achieved the following results: 61 posts were published, which, depending on the content, exceeded 5,800 views, with over 5,400 accounts reached to date; approximately 125 hours of playback in live streams hosted on the league’s YouTube channel; national reach of scientific dissemination strategies with followers from all over Brazil; positive user feedback perceived through online forms and social media metrics, thus concluding the success of the adopted strategies.